2022
DOI: 10.3390/biomedicines10030714
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease Augments Cardiovascular Disease Risk Biomarkers in Rheumatoid Arthritis

Abstract: Objectives: Periodontal disease (PD) and rheumatoid arthritis (RA) are kno­wn chronic conditions with sustained inflammation leading to osteolysis. Cardiovascular diseases (CVD) are frequent comorbidities that may arise from sustained inflammation associated with both PD and RA. In order to determine CVD risk, alterations at the molecular level need to be identified. The objective of this study, therefore, was to assess the relationship of CVD associated biomarkers in RA patients and how it is influenced by PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…To our knowledge, this is the first study showing a link between higher EN-RAGE concentrations and abnormal cardiac function. Higher concentrations of VSIG2, a protein involved in lipid metabolism, have previously been associated with coronary artery disease in patients with rheumatoid arthritis and obstructive pulmonary disease [28][29][30]. Interestingly, VSIG2 was the only of the four proteins that appeared to be inversely associated with an abnormal MPI, such that higher concentrations of VSIG2 were observed in individuals with a normal vs. abnormal MPI.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, this is the first study showing a link between higher EN-RAGE concentrations and abnormal cardiac function. Higher concentrations of VSIG2, a protein involved in lipid metabolism, have previously been associated with coronary artery disease in patients with rheumatoid arthritis and obstructive pulmonary disease [28][29][30]. Interestingly, VSIG2 was the only of the four proteins that appeared to be inversely associated with an abnormal MPI, such that higher concentrations of VSIG2 were observed in individuals with a normal vs. abnormal MPI.…”
Section: Discussionmentioning
confidence: 97%
“…Sun et al have shown that B cells affect osteoblast differentiation through a high expression of CCL3 and proinflammatory factors which further inhibit bone formation in RA [10]. Based on protein-protein interactions (PPI) showing a network of 43 CVD-related biomarkers, CCL3 was identified as increased in patients with RA and periodontal disease [11]. Those findings provide vivid evidence for the role of CCL3 in the pathogenesis and immune regulation of RA.…”
Section: Introductionmentioning
confidence: 91%
“…In patients with rheumatoid arthritis, XCL1 manifests itself in the synovium, while XCR1 is a characteristic feature of infiltrating mononuclear and synovial cells. 78 Furthermore, increased expression of XCL1 has been observed in tissues affected by Crohn's disease and in inflammatory responses of diabetic mice. 79 , 80 These findings collectively suggest that the expression of XCL1 and XCR1 increases in various sterile inflammatory diseases in humans and mice.…”
Section: The Role Of the Xcl1‐xcr1 Axis In Tbi And Scimentioning
confidence: 99%
“…In particular, the XCL1‐XCR1 axis plays a significant role in the pathogenesis of rheumatoid arthritis by inducing Th1‐mediated pro‐inflammatory responses. In patients with rheumatoid arthritis, XCL1 manifests itself in the synovium, while XCR1 is a characteristic feature of infiltrating mononuclear and synovial cells 78 . Furthermore, increased expression of XCL1 has been observed in tissues affected by Crohn's disease and in inflammatory responses of diabetic mice 79,80 .…”
Section: The Role Of the Xcl1‐xcr1 Axis In Tbi And Scimentioning
confidence: 99%